Health impacts and economic costs of residential fires (RESFIRES study): protocol for a population-based cohort study using linked administrative data - Lara A Harvey; Nargess Ghassempour; Mark Whybro; W Kathy Tannous (BMJ Open)
Introduction Residential fires remain a significant global public health problem. It is recognised that the reported number of residential fires, fire-related injuries and deaths significantly underestimate the true number. Australian surveys show that around two-thirds of respondents who experience a residential fire are unwilling to call the fire service, and international studies highlight that many individuals who access medical treatment for fire-related injuries do not have an associated fire incident report. The objectives of this study are to quantify the incidence, health impacts, risk factors and economic costs of residential fires in New South Wales (NSW), Australia.Methods and analysis The RESFIRE cohort will include all persons living at an NSW residential address which experienced a fire over the period 2005–2014. Nine data sources will be linked to provide a comprehensive picture of individual trajectories from fire event to first responder use (fire and ambulance services), emergency department presentations, hospital admissions, burn out-patient clinic use and death. These data will be used to describe the circumstances and characteristics of residential fires, provide a profile of fire-related injuries, examine trends over time, and explore the relationship between fire circumstance, emergency and health services utilisation, and health outcomes. Regression modelling, including multilevel modelling techniques, will be used to explore factors that impact on these relationships. Costing models will be constructed.Ethics and dissemination Ethical approval for this study has been obtained from the NSW Population and Health Service Research Ethics Committee and Western Sydney University Human Research Ethics Committee. The study reference group comprises key stakeholders including Fire and Rescue NSW, policy agencies, health service providers and burns clinicians ensuring wide dissemination of results and translation of data to inform practice and identify areas for targeted prevention. Summary reports in formats designed for policy audiences in parallel with scientific papers will be produced.